Implementasi Implementasi Sistem Manajemen Mutu ISO 21001: 2018 sebagai Strategi Pendidikan di Era Digital - Rahma, Rahmawati; Gresinta, Efri; Suhendra, Suhendra; Risdiana, Aan (AGUSPATI Research Institute, 2024)
The quality of education is an orientation in the implementation of education by all education stakeholders. The education quality assurance system is an important issue that is currently being discussed, it has even become the main agenda in the world of education, so it needs to be managed professionally. This research aims to find and describe the implementation of a quality management system as an education strategy in the digital era. This research uses a qualitative approach with descriptive methods. The research results concluded that the implementation of a quality management system as an educational strategy in the digital era related to determining, implementing, evaluating, controlling and improving (PEPP) has resulted in continuous improvements. This is found in the annual self-evaluation report which is used as the basis for developing strategic plans, operational plans, master development plans, budget plans and annual work plans; but not yet a complete unity. Therefore, it is recommended for the world of education to use a systems approach as a basis for thinking, how to manage, and how to analyze institutional life as a whole.